2021
DOI: 10.12659/msm.932788
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccination and Its Associated Factors Among Cancer Patients Attending the Oncology Clinic of University Clinical Hospital Mostar, Bosnia and Herzegovina: A Cross-Sectional Study

Abstract: Background The pandemic of Coronavirus infectious disease 2019 (COVID-19) poses a major public health challenge, and an effective vaccine is the potential mechanism to resolve this specific situation. The present study aimed to evaluate acceptance of COVID-19 vaccination among patients attending the Oncology Clinic of University Clinical Hospital Mostar. Material/Methods This cross-sectional observational study enrolled 364 patients with cancer from the Oncology Clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…According to the data from the Institute for Public Health of the Federation of Bosnia and Herzegovina, in the period from 3 March 2021 to 16 January 2022, only 28.20% of the population has been fully vaccinated, while 7.47% received a booster dose [ 32 , 39 ]. Marijanovic et al showed that most cancer patients (62.2%) had a hesitancy toward immunization with COVID-19 vaccines through their cross-sectional study conducted at the Clinic of Oncology, Mostar, Bosnia and Herzegovina [ 44 ]. Although we had a small sample of patients from this area of Bosnia and Herzegovina, our results are compatible since 40% of patients from the Herzegovina-Neretva Canton were adequately vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…According to the data from the Institute for Public Health of the Federation of Bosnia and Herzegovina, in the period from 3 March 2021 to 16 January 2022, only 28.20% of the population has been fully vaccinated, while 7.47% received a booster dose [ 32 , 39 ]. Marijanovic et al showed that most cancer patients (62.2%) had a hesitancy toward immunization with COVID-19 vaccines through their cross-sectional study conducted at the Clinic of Oncology, Mostar, Bosnia and Herzegovina [ 44 ]. Although we had a small sample of patients from this area of Bosnia and Herzegovina, our results are compatible since 40% of patients from the Herzegovina-Neretva Canton were adequately vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Variables specific to Eastern Europe that predict the willingness to vaccinate have also been highlighted. Several studies explored the hesitancy toward COVID-19 vaccination in Eastern European populations with comorbidities or pregnancy [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most patients appear to follow their oncologist's vaccine recommendations, indicating that the oncologist's influence is significant. A cross-sectional survey of 364 adult patients with cancer in Bosnia and Herzegovina found that 85.60% of study participants were willing to follow their oncologist's guidance on COVID-19 vaccination (26).…”
Section: Introductionmentioning
confidence: 99%